Effects of terrain‐following vertical coordinates on simulation of stratus clouds in numerical weather prediction models. (2nd October 2020) - Westerhuis, Stephanie; Fuhrer, Oliver; Bhattacharya, Ritthik; Schmidli, Jürg; Bretherton, Christopher
Abstract: Many numerical weather prediction models employ terrain‐following vertical coordinates. As a consequence, over orography, flat tops of stratus clouds are intersected by the vertical coordinate surfaces. We conduct idealised two‐dimensional simulations of a stratus cloud with the COSMO model to study the effect of such sloping vertical coordinate surfaces. The evolution of the stratus cloud above a flat surface within a horizontally homogeneous atmosphere serves as a reference. During night‐time, the cloud thickens, driven by radiative cooling at the cloud top. Adding a sinusoidal perturbation to the vertical coordinate surfaces reduces the growth of the stratus cloud. With strong perturbations, the cloud starts to dissipate. The physical processes in the two simulations are identical, hence this behaviour is purely driven by numerical diffusion. The cloud is similarly thinned when sinusoidal orographic features are introduced. The reduction depends on the amplitude and wavelength of the perturbations and hills. Increasing the horizontal resolution partly mitigates the numerical diffusion. However, this is a very costly measure for an operational weather model. We suggest conducting further research on a new vertical coordinate with additional local smoothing of the orographic signal. Abstract : In regions with complex orography, terrain‐following vertical coordinates exhibit strongly sloping coordinate surfaces aloft. Sloping coordinate surfaces typically lead to spurious numerical diffusion from the horizontal advection scheme if significant wind is present. Using idealised simulations of a stratus cloud we show how the evolution of the cloud is affected significantly by the amplitude and wavelength of the features in the vertical coordinates.